Report of a case of cavernous haemangioma of the cavernous sinus - Ibrahim, Dalia (BJR Case Rep, 2019)
Cavernous haemangioma of the cavernous sinus is a rare vascular malformation. It's often confused with other parasellar masses. Here, we report a case of a female with a left parasellar mass which was misdiagnosed as schwannoma vs meningioma using CT and MRI. The patient was operated via the pterional approach but resection had been halted due to severe haemorrhage and only tumour biopsy could be obtained. The diagnosis of cavernous sinus haemangioma was established by histopathology and confirmed by subsequent digital subtraction angiography. The patient refused second surgery or adjuvant radiosurgery and the treatment strategy was observation and follow-up. Retrospectively, we included the key radiographic features of cavernous sinus haemangioma which would facilitate pre-operative diagnosis and avoid unforeseen operative complications. Diagnostic radiographic features include a well-defined mass in the cavernous sinus which shows isodense to slightly hyperdense attenuation on non-contrast CT scan with possible adjacent pressure bone remodelling. On MRI, it shows remarkable high T(2) signal; intense homogenous enhancement or characteristic progressive contrast enhancement on sequential enhanced images. On digital subtraction angiography, it may demonstrate a vascular blush.